2022
DOI: 10.3389/fnbeh.2022.835680
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on Inter-Individual Variability of Olfactory Circuits in Drosophila

Abstract: Inter-individual differences in behavioral responses, anatomy or functional properties of neuronal populations of animals having the same genotype were for a long time disregarded. The majority of behavioral studies were conducted at a group level, and usually the mean behavior of all individuals was considered. Similarly, in neurophysiological studies, data were pooled and normalized from several individuals. This approach is mostly suited to map and characterize stereotyped neuronal properties between indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Consistent with this idea, animalto-animal variations in neural circuitry have been noted in grasshoppers 92 , crabs [93][94][95][96][97] , lobsters 98,99 , flies 31,100,101 , and rats 102 . Moreover, inter-animal variations in neuronal architecture are one of several features implicated in interanimal behavioral variations 101,[103][104][105][106]108 . However, despite this variability, overall neuronal circuit functions persistsuch as the consistent MIP-induced decrease in DM2 and DM5 OSN responses (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, animalto-animal variations in neural circuitry have been noted in grasshoppers 92 , crabs [93][94][95][96][97] , lobsters 98,99 , flies 31,100,101 , and rats 102 . Moreover, inter-animal variations in neuronal architecture are one of several features implicated in interanimal behavioral variations 101,[103][104][105][106]108 . However, despite this variability, overall neuronal circuit functions persistsuch as the consistent MIP-induced decrease in DM2 and DM5 OSN responses (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…While frequently frustrating for researchers, behavioural variability is now being explored as an inherently interesting phenomenon, through examination of the individuality of olfactory responses of genetically identical individuals [235]. Conceptually, inter-individual variation in olfactory behaviour could be due to structural and functional differences at many levels of the olfactory circuitry [236]. Although the D. melanogaster olfactory system is considered to be largely genetically hard-wired, differences between isogenic animals [75,97,106] may result from imprecision in developmental processes [237] and/or fluctuations in the internal state of the animal impacted by a plethora of factors (e.g.…”
Section: Behaviourmentioning
confidence: 99%
“…Historically, interindividual differences in animal behavior and the function of neural circuits that underlie these behaviors have been disregarded, and most studies have examined the average behavioral response and the mean activity of the neural circuits involved (Asahina et al 2022). Yet, recent studies have shown that behaviors as simple as reflexes or as complex as physiological responses to psychedelics can vary significantly among individuals (Cerins et al 2022;Moujaes et al 2022;Xu et al 2022), even when accounting for genotype and other variables (Hageter et al 2021;Palavicino-Maggio and Sengupta 2022;Rihani and Sachse 2022). Behavioral variability results largely from variability of underlying neural circuits (Feierstein et al 2015;Rihani and Sachse 2022;Tamvacakis et al 2022) and such variability is present even in smaller invertebrate neural circuits (Goaillard et al 2009;Goaillard and Marder 2021;Hamood and Marder 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, recent studies have shown that behaviors as simple as reflexes or as complex as physiological responses to psychedelics can vary significantly among individuals (Cerins et al 2022;Moujaes et al 2022;Xu et al 2022), even when accounting for genotype and other variables (Hageter et al 2021;Palavicino-Maggio and Sengupta 2022;Rihani and Sachse 2022). Behavioral variability results largely from variability of underlying neural circuits (Feierstein et al 2015;Rihani and Sachse 2022;Tamvacakis et al 2022) and such variability is present even in smaller invertebrate neural circuits (Goaillard et al 2009;Goaillard and Marder 2021;Hamood and Marder 2014). Despite significant variability, a neural circuit can generate an output that is "good enough" (Nassim 2018) to produce a related behavior, such as in the asynchronous CNS control of fly flight (Boettiger and Furshpan 1952).…”
Section: Introductionmentioning
confidence: 99%